Exploring English Culture Through English Language Books - Kadhim, Hadeer Munir Abdul Amir (Journal of Ecohumanism, 2025)
It is common to overlook or perceive culture as an extra component in EFL teaching. Modern linguistic theories emphasize the importance of focusing on culture as an essential part of language teaching. Since The communication approach was relied upon in teaching language at the end of the sixties, the concept of communicative competence has been highlighted, which many researchers believe develops not only through learning language skills, but We also mention this as well actual language interaction (Richards and Rodgers, 2001).Kramsch From his perspective, culture is not considered a “fifth skill” that is part of the skill traditional skills (speaking, listening, reading, and writing), but rather represents a background that exists from the beginning of language learning, causing changes in learners’ perception of language and revealing the limits of their communicative competence (Kramsch, 1993: 1). Tseng's sociolinguistic perspective links language and culture, highlighting that language proficiency involves not only grammatical accuracy but also the ability to use language appropriately in various contexts. He believes that understanding the culture that underlies a language is essential for successful language learning (Tsing, 12: 2002).